Web Service Integration in the Extended Logistics Enterprise - Talevski, Alex; Dillon, Tharam S.; Chang, Elizabeth (IEEE, 2003)
Transportation and warehousing logistics are activities that require strong information systems and computer support. This IT support has expanded with the advent of e-commerce. This has led to the development of e-commerce based systems by companies such as FedEx and UPS which allow their customers to track and monitor the fulfillment of their service on the Internet, provided the goods are being handled by the one corporation, with an integrated system. However, with the advent of B2B (Business to Business) and P2P (Partner to Partner) e-commerce, there has been an increasing tendency to set up consortia that represent several players in a given field. Such consortia consist of companies or organizations in a given field that get together and produce a single site in order to increase traffic through the site compared to other competitor sites and/or extend beyond their region of operation. A new form of collaboration is likely to develop in the near future leading to the concept of an extended logistics enterprise. This extended logistics enterprise provider assembles a number of companies (or Partners) that are physical logistic providers into strategic alliances that allow sharing of their facilities. This paper deals with the concept of the extended logistics enterprise and explores the software engineering issues underlying the development of such complex systems.